Desenvolvimento de um modem multimodo baseado em fpga para aplicações em rádio definido por software - Duarte Júnior, José Garibaldi (Universidade Federal Rural do Semi-Árido, 2018)
With the development of communication technologies, many existing standards are mainly due to their application areas. As a result, there is a need for systems that can operate satisfactorily between different communication schemes, thus providing a greater interaction between applications. Software Defined Radio (SDR) is a radio communication system that allows the use of a general architecture for different communication standards through adjustments via code or some similar interface. In order to enable SDR interactions between schemes, a modem that operates multiple modulation patterns is required. This work presents the development and implementation in FPGA of a modem operating in digital amplitude (ASK), frequency (FSK) and phase (PSK) modulation schemes. The architecture of the Multimode Modem was designed through a hardware description language, thus allowing adjustments through code that would allow to change the operation of the system. In order to enable the modem tests, auxiliary circuits were implemented, being a Digital-Analog converter of the type R2R Ladder, a Sigma- Delta Analog-Digital converter with Fitro CIC and a bit generator. Modem prototyping was performed on a FPGA model Cyclone III together with the DE-0 development board. Based on a 50 MHz clock, 9-bit resolution waveforms were obtained between 830 kHz and 1.66 MHz, while still obtaining modulated signals with a bandwidth of 200 kHz for ASK modulation and 820 kHz for FSK. With the synthesis of the code, it was verified the possibility of operating the architecture up to 146 MHz, using a total of 34 % of the total processing capacity of the FPGA in question. Therefore, the architecture developed was satisfactory in the process of modulation and demodulation of signals in relation to the basic modulation schemes in a configurable way, allowing its use in conjunction with Software Defined Radio systems.
Monografia
Keywords: Rádio Definido por Software; Modem; A/D; D/A; FPGA; VHDL; ENGENHARIAS::ENGENHARIA ELETRICA